Non Abelian T-duality and Holography. - Niall Thomas Macpherson (2014)
"We study non-abelian T-duality as a supergravity solution technique and explore its application to holography. We consider well understood geometries which describe the strong coupling regime of minimally supersymmetric gauge theories in 3 and 4 dimensions. We then use non-abelian T-duality to generate new solutions in type-II supergravity and use these to define new gauge theories with interesting dynamics such as confinement. The work contains extensive field theoretic analysis of these new solutions. We explore how the supersymmetry of the "seed" solutions is preserved under T-duality transformations by employing the powerful techniques of G- structures and generalised geometry. As well as giving a geometric description of non-abelian T-duality, this also enables us to extend the duality to cases with calibrated sources. We find that quite generically SU(3)-structures in 6d are mapped to SU(2)-structures. Further we find an intimate relationship between dynamic SU(2)-structures and confinement in these new solutions."